The influence of agroforestry silviculture on productivity and quality of Canna edulis Ker on private forest land - Sudomo, A; Hani, A (Journal of Degraded and Mining Lands Management, 2014)
The productivity of private forest land by using agroforestry of Canna edulis Ker aims to achieve food security at the smallholder level. The purpose of this study was to determine the effect of agroforestry cropping patterns on productivity and quality of Canna edulis Ker tuber on private forest land. The study was conducted in dry area of the private forest land who are administrativelyincluding Tenggerraharja Village area, SukamantriSubdistrict, Ciamis District, West Java Province, Indonesia. The planting of Canna edulis Ker was implemented under the 32 months old Manglieta glauca BI stands. The main plots were three pruning intensity of Manglietia glauca BI stands i.e. P0 (0 % ) , P1 (50%), and P2 (75%). The sub plots were three planting spaces of Manglietia glauca BI, i.e. S1 (2m x 2m), S2 (2m x 3 m), and S3 (3m x 3m). The planting of Canna edulis Ker by monoculture technique was conducted as a comparison. The results showed that the interaction of planting space and pruning intensity gave a significant result on height growth, wet weight and dry weight of plant, wet weight and dry weight of Canna edulis Ker tuber. The growth of Canna edulis Ker that ranged from 181.85 cm (P0S1) to 186.30 cm (P1S1) were higher than the monoculture system on Canna edulis Ker (138.20 cm). The wet weight and dry weight of tuber that ranged from 2089.3 g and 1429.99 g (P2J2) to 3695.5 g and 2678.09 g (P1S2), whreas those in the monoculture system on Canna edulis KerÂ  were 2363.1 g and 1528.7 g. However, the protein, fiber and carbohydrate contents of P0S1, P1S1, P2S1 treatments were lower than those of the monoculture system on Canna edulis Ker. The planting pattern of agroforestry were able to improve the plant height of Canna edulis Ker tuber but giving less percentage of carbohydrate and protein of tuber than the monoculture.